International Association of Technological University Libraries (IATUL): Promoting Science and Technology Librarianship in the Changing Library Landscape - Maitrayee Ghosh (Türk Kütüphaneciliği)
International Association of Technological University Libraries (IATUL) has been in the forefront of providing leadership to information professionals and promoting science and Technology librarianship in today's changing library landscape. The present article is an attempt to comprehend the present status of IATUL and analyze the activities and contribution it has made to overcome the range of challenges facing by tertiary level Technological libraries throughout the world. The SWOT analysis method is used to assess the achievements of IATUL, failures and ascertain constraints being faced in this internet age. The author relied on web sites as well as ephemeral material such as minutes, annu- al reports, newsletters, and memoranda to construct this article. Meeting and Interview with IATUL present and past presidents and other office bearers of the associations provided useful sources of information. It is also attempted to pro- vide relevant information for those interested to join IATUL for professional development.